2017
DOI: 10.18632/oncotarget.17805
|View full text |Cite
|
Sign up to set email alerts
|

FAM3A mediates PPARγ's protection in liver ischemia-reperfusion injury by activating Akt survival pathway and repressing inflammation and oxidative stress

Abstract: FAM3A is a novel mitochondrial protein, and its biological function remains largely unknown. This study determined the role and mechanism of FAM3A in liver ischemia-reperfusion injury (IRI). In mouse liver after IRI, FAM3A expression was increased. FAM3A-deficient mice exhibited exaggerated liver damage with increased serum levels of AST, ALT, MPO, MDA and oxidative stress when compared with WT mice after liver IRI. FAM3A-deficient mouse livers had a decrease in ATP content, Akt activity and anti-apoptotic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
(54 reference statements)
1
35
0
Order By: Relevance
“…12,13 FAM3A is a target gene of peroxisome proliferator-activated receptor gamma (PPARγ), and it mediates the beneficial effects of PPARγ's activation on liver ischemia/reperfusion injury. 15,16 Beyond liver, FAM3A also regulates the functions of vascular smooth muscular cells (VSMCs) and adipocytes by modulating ATP-Akt pathways. 17,18 FAM3A also protects neuronal cells against apoptosis triggered by oxidative and endoplasmic reticulum (ER) stress.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 FAM3A is a target gene of peroxisome proliferator-activated receptor gamma (PPARγ), and it mediates the beneficial effects of PPARγ's activation on liver ischemia/reperfusion injury. 15,16 Beyond liver, FAM3A also regulates the functions of vascular smooth muscular cells (VSMCs) and adipocytes by modulating ATP-Akt pathways. 17,18 FAM3A also protects neuronal cells against apoptosis triggered by oxidative and endoplasmic reticulum (ER) stress.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is the lack of oxygen supply to tissues, which results in abnormal cell metabolism and function as well as pathological morphological alterations . The aetiology of hypoxia‐related diseases is complex and can be divided into four categories: hypoxic hypoxia induced by an arterial oxygen pressure drop, circulatory hypoxia caused by tissue blood flow reduction, hemic hypoxia induced by haemoglobin reduction and dysoxidative hypoxia caused by altered bio‐oxidation of tissues .…”
Section: Introductionmentioning
confidence: 99%
“…In cultured hepatocytes, ATPSβ overexpression similarly activated the PI3K-Akt pathway via ATP-P2 receptor-CaM signaling transduction independent of insulin [45]. Importantly, FAM3A and ATPSβ overexpression promoted the nuclear exclusion of FOXO1 in P2 receptor-dependent manner in cultured hepatocytes [45,46]. Collectively, these findings strongly suggested that the ATP-P2 receptor signaling pathway plays important roles in the regulation of Akt and FOXO1 activities, and subsequent glucose and lipid metabolism in hepatocytes independent of insulin.…”
Section: Fam3a Represses Hepatic Gluconeogenesis and Lipogenesismentioning
confidence: 80%